Anti-ultraviolet, antibacterial, and biofilm eradication activities against Cutibacterium acnes of melanins and melanin derivatives from Daedaleopsis tricolor and Fomes fomentarius - Le, Tu N.; Tran, Ngan T. H.; Pham, Vy N. T.; Van-Thi, Ngoc-Dung; Tran, Hanh T. M. (Frontiers in Microbiology, 2024)
Fomes fomentarius and Daedaleopsis tricolor produced significant amounts of water insoluble melanins, and our previous study successfully enhanced their water solubility by arginine modification. This research aimed to investigate anti-ultraviolet, antibacterial, and biofilm eradication activities of both the melanins and arginine modified melanin (melanin derivatives) from these two fungi against an acne causing bacterium (Cutibacterium acnes). Apart from these, the cytotoxicity of the melanins and melanin derivatives on human skin cells was also evaluated.Melanin derivatives of both two fungi showed significantly higher antibacterial and biofilm eradication activities compared with their original forms. Specifically, the MIC50 values of the melanin derivatives (1000 μg/mL) are the same with Erythromycin. Regarding biofilm eradication capacity, the MBEC50 value of D. tricolor melanin derivative (250 μg/mL) was just half of both Erythromycin and F. fomentarius melanin derivative. However, it required a twofold higher concentration of melanin derivatives than Erythromycin to inhibit 90% of the bacterial population and eradicate 90% of their biofilm. Regarding anti-ultraviolet activity, blending melanins or melanin derivatives with a moisturizer/sunscreen enhanced their UV light absorption and the Sun Protection Factor (SPF) values.In addition, melanins showed better effects than their derivatives and those of D. tricolor were better than F. fomentarius. Remarkably, adding D. tricolor melanin (10%) into a Nivea pure cream could turn this cream into a broad-spectrum sunscreen with its SPF value and critical wavelength increased from 7.74 and 338.67 to 14.02 and 377.0, respectively. In addition, adding melanin or melanin This is a provisional file, not the final typeset article derivative of D. tricolor to an Olay sunscreen enhanced the SPF and the critical wavelength of the sunscreen from 17.25 and 371.67 to 23.82 and 374 and 23.38 and 372, respectively. Notably, melanins and melanin derivatives showed no toxicity on human fibroblasts.The obtained data suggest that arginine modification significantly enhanced the antibacterial and biofilm eradication activities of melanins from D. tricolor and F. fomentarius. However, this is not the case when it comes to their anti-ultraviolet activities. In addition, melanin and melanin derivatives from D. tricolor are potential candidates for antiacne sunscreen products and are worth further investigation.